The Invention Of Writing In Nile valley [c.3100 BC] (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Ancient Egyptian reached to invention the writing as a way to express on his ideas about 3100 BC by writing he recorded the important events ,customs and traditions in his life ,by various graphics that included letters had status of intellectual ,photographic, and symbolic ,it was used over Ancient Egypt history .These letters have taken characters of ;humans, animals, plants, tools, and various  characters of Ancient Egyptian human environment , that was wrote on temples, tombs, stone tablets, papyrus, woods ,pottery, seals. Egyptians considered it made by Gods ,so they looked to it as divine writing so called it "medut netcher" it means word of God .Then later Greeks called it "Hieroglyphic" it means holy  engraving .According to the view of researcher Hieroglyphic belong to the "Afro-Asiatic" family. The historical stages of Hieroglyphic had development in its form  and structure ;began to Hieratic  line, Demotic line, then Coptic line.